(untitled) (Journal of the College of Education for Women, 2019)
Abstract:This research (The effect of information in Iraqi universities) wants toexplain the aims and the opinions of Iraqi universities lecturers during theglobalization era and information technology .The results we have got about using the computers by the lecturers ofIraqi universities just in illustration and statistic as depends on there works